Spontaneous Self‐Practice of Cognitive Behavioural Therapy (CBT) by Aboriginal Counsellors During and Following CBT Training: A Retrospective Analysis of Facilitating Conditions and Impact. (October 2015) - Bennett‐Levy, James; Wilson, Shawn; Nelson, Jeff; Rotumah, Darlene; Ryan, Kelleigh; Budden, Wayne; Stirling, Janelle; Beale, Dean
Abstract : Previous cognitive behavioural therapy (CBT) training studies have suggested that therapists who practice CBT strategies on themselves during training may experience professional and personal benefits. However, it has also been reported that some CBT trainees are reluctant to engage in self‐practice. The present study reports an incidental finding from a CBT training study with Aboriginal counsellors: all five counsellors reported that they practiced CBT techniques on themselves without specific encouragement by the trainers to do so. This paper therefore posed three questions: (a) Why—in contrast to some other trainees—did this group choose to apply CBT to themselves? (b) How did they apply it—with what purpose, in what contexts, and which skills? (c) What was the impact of CBT self‐practice? Data from the group's reflections were qualitatively analysed by two of the researchers, and "member checked" by the remainder. Results indicated that the counsellors were motivated to practice CBT on themselves for two principal reasons: the value they placed on CBT, and their personal need resulting from the high number of crises experienced while living and working in their communities. The counsellors reported practicing CBT in a wide variety of contexts as part of their learning. As in previous studies, the impact of CBT self‐practice was that it increased their confidence and competence as therapists. It also appeared to be a valuable burnout prevention strategy. If the results are generalisable, they suggest that self‐experiential training in CBT may be a culturally responsive and adaptive way for Aboriginal counsellors to enhance their learning of CBT skills.